Complete sequencing of plasmids containing blaOXA-163 and blaOXA-48 in Escherichia coli sequence type 131. - Stoesser, N; Sheppard, AE; Peirano, G; Sebra, R; Lynch, T; Anson, L; Kasarskis, A; Motyl, MR; Crook, DW; Pitout, JD (American Association for Microbiology, 2016)
OXA-48-like enzymes have emerged as important extended-spectrum β-lactamases/carbapenemases in Escherichia coli sequence type 131 (ST131). We report the structures of the first fully sequenced blaOXA-163 plasmid and of two other blaOXA-48 plasmids in this lineage. blaOXA-163 was located on a 71-kb IncN plasmid with other resistance genes. blaOXA-48 was present on IncL/M plasmids, genetically similar to other blaOXA-48 plasmid sequences, and consistent with interspecies/interlineage spread. The presence of blaOXA-48-like genes on epidemic plasmids in ST131 is of concern.